Handling of Violent Crimes Between Community Groups in Ternate Conducted by the Police - Muhammad Rizkal Kunio; Ridjal Junaidi Kotta; Nam Rumkel (Khairun Law Journal, 2019)
Efforts to tackle crime in general can be divided into two, namely the path of punishment (criminal law) and through non-punishment (not / outside of criminal law). The two pathways can be distinguished that, with efforts to overcome through the penalty line more focused on the repressive nature (oppression / eradication / suppression) after the crime occurred, while the non-penal route is more focused on the nature of the prefentive (prevention / deterrence / control) before the crime occurred. This research was conducted to find out what are the factors causing the occurrence of acts of violence between community groups in Toboko and Mangga Dua in Ternate City as well as the form of handling conducted by the Police Resort of Ternate on the issue. The results of the research in the field found that there were 2 (two) factors that caused violence between Toboko and Mangga Dua groups, namely group factors and individual factors, while the form of handling undertaken by the Ternate Resort Police was by taking preventive measures and repression.